Diffusion in Cauchy Elastic Solid - Danielewski, Marek; Sapa, Lucjan (Diffusion Fundamentals, 2022)
It is commonly accepted that a starting point of the science of diffusion is the phenomenological diffusion equation postulated by German physiologist Adolf Fick inspired by experiments on diffusion by Thomas Graham and Robert Brown. Fick’s diffusion equation has been interpreted decades later by Albert Einstein and Marian Smoluchowski. Here we will show that the theory of diffusion has its elegant mathematical foundations formulated three decades before Fick by French mathematician Augustin Cauchy ( 1822). The diffusion equation is straightforward consequence of his model of the elastic solid - the classical balance equations for isotropic, elastic crystal. Basing on the Cauchy model and using the quaternion algebra we present a rigorous derivation of the quaternion form of the diffusion equation. The fundamental consequences of all derived equations and relations for physics, chemistry and the future prospects are presented.